Atrial appendages’ mechanics assessed by 3D transoesophageal echocardiography as predictors of atrial fibrillation recurrence after pulmonary vein isolation - Zeljković, Ivan (Int J Cardiol Heart Vasc, 2020)
BACKGROUND: Although there are numerous studies reflecting predictors of atrial fibrillation (AF) recurrence (AFR) after pulmonary vein isolation (PVI), data on atrial appendages' mechanics is scarce. This study aimed to assess atrial appendages' mechanics by 2-dimensional (2D) and 3-dimenssional (3D) transoesphageal echocardiography (TEE) and to explore its value to predict AFR after PVI. METHODS: Consecutive patients with paroxysmal AF undergoing first PVIwere analysed. 3D and 2D-TEE with tissue Doppler imaging (TDI) and strain analysis was obtained prior to the PVI, including: left atrial appendage (LAA) TDI and strain analysis, LAA ostium surface area, right atrial appendage’s TDI velocity and superior vena cava (SVC) ostium surface area. The primary end-point was freedom from any documented recurrence of atrial arrhythmia lasting > 30 s. RESULTS: This single-centre, prospective study included 74 patients with paroxysmal AF (median age 59 years; 36% female; BMI 27.4 ± 4.1 kg/m(2), LA volume index 32 ± 11 mL/m(2)). After a median follow-up of 14 (IQR 10–22) months, 21 (28%) patients had AFR. In a univariate and multivariate Cox-regression analysis LAA TDI velocity (HR 1.48, 95%CI 1.28–1.62, p < 0.001) and LAA ostium surface area(HR 1.58, 95%CI 1.06–1.81, p = 0.033) both independently predicted AFR after single PVI. RAA TDI velocity and SVC ostium surface area were not correlated to AFR. CONCLUSION: Paroxysmal AF patients with lower LAA TDI tissue velocity and LAA ostium surface area have higher risk of developing AFR after PVI. To our knowledge, this is the first study assessing atrial appendages’ mechanics in predicting AFR after PVI. Clinical trial registration: www.drks.de(Identifier: DRKS00010495)